A trial-ready cohort for finding unmet needs and improving quality of life among patients with esophageal cancer: a multicenter prospective cohort study - Han, Jiyoon; Lee, Genehee; Cho, Juhee; You, Somin; Shim, Young Mog; Choi, Yong Soo; Cho, Jong Ho; Park, Seong Yong; Jeon, Yeong Jeong; Lee, Junghee; Kang, Danbee; Kim, Hong Kwan (Frontiers in Oncology, 2025)
Although esophageal cancer survivors experience lower health-related quality of life (HRQoL), it is hard to provide proper supportive care due to difficulties to find potential target population. This study aims to develop a trial-ready cohort (TRC) to assess the unmet needs and HRQoL of survivors of esophageal cancer. This prospective, multicenter TRC study will include 600 patients diagnosed with primary esophageal cancer who have undergone curative treatment. Exclusion criteria include the presence of synchronous malignancies, severe cognitive impairment, and residence outside of Korea. Patients are recruited from both existing cohort studies and newly diagnosed cases beginning in June 2023. At the time of enrollment into the TRC, participants provide informed consent, including agreement to be contacted and considered for relevant clinical trials when suitable interventions become available. Data is collected across five domains: sociodemographic characteristics, health behaviors, disease and treatment information, nutritional status, and quality of life. Study visits are scheduled at diagnosis, prior to surgery, at 1, 3, 6, and 12 months post-surgery, and annually thereafter for up to 10 years. As of June 2025, a total of 448 participants have been enrolled, representing approximately 75% of the target. To achieve this, our TRC employs three key strategies. First, we leverage three existing prospective studies to efficiently identify and enroll long-term survivors. Second, we collect a wide range of data on HRQoL, health behaviors, and environmental factors to enable a multidimensional understanding of survivorship. Third, we collect multiple times within short-term interval points, allowing seamless linkage between the cohort and appropriate trials. This study effectively designs a trial-ready cohort of survivors of esophageal cancer using a unique strategy to overcome cohort construction challenges, aiming to generate valuable data on quality of life and serve as a platform for tailored interventions.